Correlation of Peritumoral Edema and Microvessel Density with Tissue Expression of VEGF, Semaphorins 3A and 3C in Patients with Meningioma - Salimi-Sotoodeh, Mehdi; Saffarian, Arash; Taghipour, Mousa; Dehghanian, Amir-Reza; Chenari, Nooshafarin; Ghaderi, Abbas; Razmkhah, Mahboobeh (Asian Pacific Journal of Cancer Biology, 2019)
Background: Several angiogenic factors correlate with angiogenesis in meningioma while their exact role is yet to be identified. Semaphorins are described with a variety of physiological functions including angiogenesis and migration of neural crest cells. Objective: We aimed to determine the correlation of semaphorin 3A, 3C (Sema 3A and 3C) and vascular endothelial growth factor (VEGF) expression with microvessel density (MVD) and peritumoral brain edema (PTBE) in meningioma. Methods: In this study 21 patients with grade I meningioma were included. PTBE was measured on axial and coronal brain MRI. Tissue expression of semaphorin 3A, 3C and VEGF were determined using quantitative real-time PCR (qRT-PCR). Result: We found that mean vascular density and tumor edema index were negatively associated with tissue expression of semaphorin 3A and 3C, respectively (p=0.029 and p=0.048). VEGF did not show statistically significant correlation with tumor characteristics studied (p> 0.05). We also found that the mean vascular density of the menigiomas was positively associated with intra operative blood loss (r=0.503, p=0.010). Conclusion: Our data indicates an inverse correlation of Sema3A and Sema3C with vascular density and peritumoral edema, respectively, while no correlation could be shown for VEGF. Thus, Sema3A and 3C may be identified as appropriate inhibitors of pathological angiogenesis in human meningioma. However, confirmation of this finding in a larger dataset is warranted.